2011
DOI: 10.1016/j.talanta.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of collision–reaction interface and internal standardization in quadrupole ICP-MS measurements

Abstract: The combined use of internal standardization with collision and reaction interface in an inductively coupled plasma quadrupole mass spectrometer (ICP-QMS-CRI) was evaluated. The behavior of several elements (Ba, Cd, Co, Cr, Cu, Li, Mn, Mo, Pb, Sb, V and Zn) was studied by introducing H(2) or He through the skimmer and sampler cones of the CRI device and by using In, Rh and Sc as internal standards. Certified reference material of trace elements in water (NIST 1643e) was used to evaluate the performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…Salazar et al ( 2011 ) reported the use of Sc as the best IS species for 18 out of 28 analyte isotopes evaluated. The authors argue that Sc is a good IS in ICP-MS due to the proximity of its mass and/or first ionization energy with those of the analytes.…”
Section: Traditional Calibration Methodsmentioning
confidence: 99%
“…Salazar et al ( 2011 ) reported the use of Sc as the best IS species for 18 out of 28 analyte isotopes evaluated. The authors argue that Sc is a good IS in ICP-MS due to the proximity of its mass and/or first ionization energy with those of the analytes.…”
Section: Traditional Calibration Methodsmentioning
confidence: 99%
“…Relatos sobre a toxicidade do cromo em animais terrestes são escassos, porém, WHO (1988) cita também que a toxicidade para a maioria dos microorganismos ocorre na faixa de 0,05 mg kg Segundo Macedo e Morril (2008), o Cromo, por participar dos processos metabólicos da glicose, tem sido considerado essencial para homens e animais e, por essa razão, acredita-se que a absorção do metal pelas oligochaetas foi superior em relação aos outros metais. Entretanto, quando presentes em amostras ambientais de água e solos acidificados esse elemento apresenta estado de oxidação hexavalente Cr(VI), podendo ser extremamente tóxico à biota local (Salazar et al, 2011b;Bianchi et al, 2012). Há que se considerar, ainda, a presença do metal no esterco bovino adicionado ao solo conforme propõem Gonçalves et al (2007).…”
Section: Methodsunclassified
“…Spectral and non-spectral interferences in ICP-MS can be minimized using high-resolution ICP-MS, collision/reaction cell ICP-MS and some analytical strategies such as standard additions method, isotope dilution, matrix matching and internal standardization. However, these techniques are costly and are not applicable to solve problems and they still suffer from matrix effects when samples are analyzed directly (McCurdy and Woods 2004, Salazar et al 2011). Therefore, a sample pretreatment step for eliminating the saline matrix components and extracting the analyte(s) of interest remains very attractive in ICP-MS measurements.…”
Section: Introductionmentioning
confidence: 99%